2021
DOI: 10.2196/23839
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Racially and Ethnically Diverse Women at High Risk of Breast Cancer Regarding the Use of a Web-Based Decision Aid for Chemoprevention: Qualitative Study Nested Within a Randomized Controlled Trial

Abstract: Background Chemopreventive agents such as selective estrogen receptor modulators and aromatase inhibitors have proven efficacy in reducing breast cancer risk by 41% to 79% in high-risk women. Women at high risk of developing breast cancer face the complex decision of whether to take selective estrogen receptor modulators or aromatase inhibitors for breast cancer chemoprevention. RealRisks is a patient-centered, web-based decision aid (DA) designed to promote the understanding of breast cancer risk … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“… 13 In comparison to other web‐based decision support tools, iBDecide has similar usability and acceptability. 36 , 37 , 38 , 39 , 40 This similar usability corroborates not only iBDecide's standard decision support functions but also its novel condition management features.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“… 13 In comparison to other web‐based decision support tools, iBDecide has similar usability and acceptability. 36 , 37 , 38 , 39 , 40 This similar usability corroborates not only iBDecide's standard decision support functions but also its novel condition management features.…”
Section: Discussionsupporting
confidence: 62%
“…A few other recent studies of decision aids for paediatric chronic conditions do exist, 12,35 as well as one for AYA cancer patients focused on fertility‐preservation treatments, 13,14 but only one provides usability data 13 . In comparison to other web‐based decision support tools, iBDecide has similar usability and acceptability 36–40 . This similar usability corroborates not only iBDecide's standard decision support functions but also its novel condition management features.…”
Section: Discussionmentioning
confidence: 60%
“…The acceptability for RealRisks 62 , 63 was assessed through semi-structured interviews consisting of a sample of mostly non-Hispanic (91%) White (71%) women, in which all women reported that the tool was acceptable. 67 BreastCare 52 was also assessed for feasibility.…”
Section: Resultsmentioning
confidence: 99%